2000
DOI: 10.1890/0012-9658(2000)081[0899:forfir]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Riparian Floras in Rivers With Multiple Dams

Abstract: Rivers are increasingly fragmented by dams, resulting in disruption of natural dispersal pathways and subsequent changes of riverine communities. We assessed the effect of dams as barriers to plant dispersal along rivers by comparing the flora of vascular plants between pairs of run‐of‐river impoundments in northern Sweden. Adjacent impoundments in similar environmental settings develop different riparian floras because species with poor floating capacity become unevenly distributed among impoundments. Such di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(98 citation statements)
references
References 19 publications
1
95
0
2
Order By: Relevance
“…The reservoirs created by dams can trap sediment and seeds, affecting the ability of seeds to disperse downstream, thus fragmenting the biological connectivity of riparian zones (Jansson et al 2000). For example, Merritt and Wohl (2006) found that dams reduced seed concentration in the water column by 70-94% on two rivers in the southern Rocky Mountains of Colorado.…”
Section: Introductionmentioning
confidence: 99%
“…The reservoirs created by dams can trap sediment and seeds, affecting the ability of seeds to disperse downstream, thus fragmenting the biological connectivity of riparian zones (Jansson et al 2000). For example, Merritt and Wohl (2006) found that dams reduced seed concentration in the water column by 70-94% on two rivers in the southern Rocky Mountains of Colorado.…”
Section: Introductionmentioning
confidence: 99%
“…Dams, culverts, and waterfalls (Magnuson 1978;Holmquist et al 1998;Jansson et al 2000), as well as riffles during periods of low water (Power et al 1985, Covich et al 1996 physically block within-stream movements. Biotic conditions of the stream, such as the presence of predators or competitors, limit movers (Bradford et al 1993;Covich et al 1996;García-Ramos et al 2000), as do physical factors, including water velocity, nutrient levels (Dent & Grimm 1999), temperature, dissolved oxygen, and water levels.…”
Section: Within-stream Boundaries and Corridorsmentioning
confidence: 99%
“…These transformations have disrupted natural flows that formerly occurred within ecosystems, communities, and populations (Harris & Scheck 1991) and have created new ones (Bennett 1991). Forests have been subdivided into isolated woodlots set in a matrix of agricultural land (Burgess & Sharpe 1981), rivers have been blocked by hydroelectric dams (Magnuson 1978;Holmquist et al 1998;Jansson et al 2000), and canal systems link previously isolated waterways (Mills et al 1993). Even in national parks and other protected areas, high-use trails and roads connect the exterior and interior portions of many remaining forests (Benninger-Truax et al 1992;Tyser & Worley 1992;Parendes & Jones 2000;Trombulak & Frissel 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Hydropower is a safe, low-cost, clean, sustainable source of renewable energy for many countries (Renöfalt et al, 2010;Jager and Smith, 2008;Frey and Linke, 2002) and bridges a significant gap in world energy markets by supplying a fifth of world energy consumption (Bakis, 2007). However, hydropower generation has socioeconomic and environmental implications (Demirbas, 2007;Andersson et al, 2006;Nilsson et al, 2005;Jansson et al, 2000;Dynesius and Nilsson, 1994).…”
Section: Introductionmentioning
confidence: 99%